Research on Acoustic Emission and Electromagnetic Emission Characteristics of Rock Fragmentation at Different Loading Rates. (3rd May 2018) - Zhao, Fujun; Li, Yu; Ye, Zhouyuan; Fan, Yong; Zhang, Siping; Wang, Haifan; Liu, Yonghong
Abstract : The relationships among the generation of acoustic emission, electromagnetic emission, and the fracture stress of rock grain are investigated, which are based on the mechanism of acoustic emission and electromagnetic emission produced in the process of indenting rock. Based on the relationships, the influence of loading rate on the characteristics of acoustic emission and electromagnetic emission of rock fragmentation is further discussed. Experiment on rock braking was carried out with three loading rates of 0.001 mm/s, 0.01 mm/s, and 0.1 mm/s. The results show that the phenomenon of acoustic emission and electromagnetic emission is produced during the process of loading and breaking rock. The wave forms of the two signals and the curve of the cutter indenting load show jumping characteristics. Both curves have good agreement with each other. With the increase of loading rate, the acoustic emission and electromagnetic emission signals are enhanced. Through analysis, it is found that the peak count rate, the energy rate of acoustic emission, the peak intensity, the number of pulses of the electromagnetic emission, and the loading rate have a positive correlation with each other. The experimental results agree with the theoretical analysis. The proposed studies can lead to an in-depth understanding of the rock fragmentation mechanism and help to prevent rock dynamic disasters.